1977
DOI: 10.1111/j.1151-2916.1977.tb14097.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fast Neutron Irradiation on the Structure of Boron Carbide

Abstract: The leading LMFBR control rod material, B,C, was examined by SEM, TEM, and X-ray diffraction after irradiation up to 80x lozu capturedcd between 500" and 920°C. Bulk swelling was found to be the result of elastic and plastic strains, rather than dilation of the unit cell. Microcracking was observed and explained in terms of anisotropic swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…SiC samples do not react with thermal neutrons but they can be damaged by transmutation recoils produced near the B 4 C surface. 7 Li and 4 He created by reaction (1) 4 C. This implies that the analyzed depth, here about 7 µm, is larger than the implantation range of Li, and reveals some damage ( figure 9). Now, it is known that some irradiation damage in SiC can be annealed when heated at their previous irradiation temperature [9].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…SiC samples do not react with thermal neutrons but they can be damaged by transmutation recoils produced near the B 4 C surface. 7 Li and 4 He created by reaction (1) 4 C. This implies that the analyzed depth, here about 7 µm, is larger than the implantation range of Li, and reveals some damage ( figure 9). Now, it is known that some irradiation damage in SiC can be annealed when heated at their previous irradiation temperature [9].…”
Section: Discussionmentioning
confidence: 89%
“…about 10 percent of total boron in actual fast neutron reactor conditions) produces He and Li recoils that induce defect formation during their stopping and chemical modification of the pristine boron carbide. Helium clusters in over-pressurized small bubbles could lead to inter-and intragranular cracking [4]. The fate of lithium is less clear since this element is not visible using classical methods such as Electron Probe Micro Analysis (EMPA) or X-Ray Photoelectron Spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a control rod material, the defect structure in neutron irradiated B 4 C was investigated by Ashbee [3,4], Jostsons [5,6], Hollenberg [7] and Donomae [8] et al He + implantation of B 4 C has been performed by Stoto [9] and Maruyama [10]. Irradiation effects and helium bubble formation in aluminum after high energy proton irradiation were reported by Singh and Victoria [11,12].…”
Section: Neutronsmentioning
confidence: 96%
“…3d and e), presumably on pre-existing defect. Previous works have shown that lined up or orientated helium bubbles can form during high temperature neutron irradiation or after high temperature annealing [6][7][8]. Helium bubble strings were seen when B 4 C was irradiated by 16 MeV He + at a much higher temperature (1720°C) by Stoto [9].…”
Section: Neutronsmentioning
confidence: 96%